2021
DOI: 10.1017/s1368980021002792
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional marketing of plant-based meat-analogue products: an exploratory study of front-of-pack and website claims in the USA

Abstract: Objective: To explore how some of the largest food companies involved in producing alternative proteins use health and nutrition claims to market their products. Design: We identified the largest food manufacturers, meat processors, and alternative protein companies selling plant-based alternative protein products in the United States. Using publicly available data, we analysed the voluntary health and nutrition claims made on front-of-pack labels and company webpages. We also analysed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 30 publications
0
21
1
1
Order By: Relevance
“…The same authors also found a 19 and 21% rate of products with vitamin- and mineral-related claims, respectively. This finding is pretty higher than the one found in the present survey (<4% of the total) and in the US market-based survey by Lacy-Nichols and collaborators, showing <1% of those claims ( 29 ). These last data are as interesting as weird by considering that the presence of anti-nutritional factors potentially affects mineral bioavailability.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…The same authors also found a 19 and 21% rate of products with vitamin- and mineral-related claims, respectively. This finding is pretty higher than the one found in the present survey (<4% of the total) and in the US market-based survey by Lacy-Nichols and collaborators, showing <1% of those claims ( 29 ). These last data are as interesting as weird by considering that the presence of anti-nutritional factors potentially affects mineral bioavailability.…”
Section: Discussioncontrasting
confidence: 82%
“…These values are higher than those found by an Australian survey of analogue products on the US market. Here only 49% of the products retrieved in supermarkets and 40% in online stores boasted a nutrition claim, mainly on the protein content ( 29 ). The “ Safe food” report showed that the protein-related claim in the plant-based analogues sold in Ireland was present in 50% of the products (11% “source of protein” and 39% “high in protein”) ( 26 ), while in the paper of Curtain and Grafenauer ( 25 ) this value accounted for 60% of the items.…”
Section: Discussionmentioning
confidence: 99%
“…Plant-based products tend to be marketed as healthy alternatives [23]. In general we found that whole meals available from supermarkets and delivery chains meet dietary requirements for saturated fat content, and the saturated fat content of vegan and vegetarian meals available from both fast-food and sit-down chains was also significantly lower than the meat-based meals.…”
Section: Discussionmentioning
confidence: 84%
“…Nutrition and health claims are major means of informing consumers about characteristics of food products and are also important regarding the promotion of healthy and sustainable plant-based products ( 49 ). Research has shown, though, that consumer attention to nutrition and health claims at the point of purchase is limited ( 50 ).…”
Section: Discussionmentioning
confidence: 99%